2013
DOI: 10.1245/s10434-013-2950-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of Positive Transection Margins with Gastric Cancer Survival and Local Recurrence

Abstract: Positive resection margin is associated with advanced AJCC stage and aggressive tumor biology but remains an independent predictor of worse survival. The significance of a positive margin in gastric cancer is confined to patients with nontransmural disease and/or limited nodal involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 12 publications
5
69
2
2
Order By: Relevance
“…Sun et al [3] found that locoregional relapse in patients with positive RMs was more frequent than distant or peritoneal relapse, and that it was more frequent than in negative RM patients, as expected. In contrast, Wang et al [14] and Bickenbach et al [20] showed that the main recurrence pattern in R1 resection patients was peritoneal rather than locoregional. This finding may indicate that positive RM patients generally have a more advanced and more aggressive disease [20], whose systemic impact can mask the still present locoregional effects.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Sun et al [3] found that locoregional relapse in patients with positive RMs was more frequent than distant or peritoneal relapse, and that it was more frequent than in negative RM patients, as expected. In contrast, Wang et al [14] and Bickenbach et al [20] showed that the main recurrence pattern in R1 resection patients was peritoneal rather than locoregional. This finding may indicate that positive RM patients generally have a more advanced and more aggressive disease [20], whose systemic impact can mask the still present locoregional effects.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, Wang et al [14] and Bickenbach et al [20] showed that the main recurrence pattern in R1 resection patients was peritoneal rather than locoregional. This finding may indicate that positive RM patients generally have a more advanced and more aggressive disease [20], whose systemic impact can mask the still present locoregional effects. In addition, in our study we found that patients with positive RMs had clinicopathological features significantly more advanced and more aggressive than those of R0 resection patients, especially concerning T category, N category, grading, and Lauren pattern.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Multiple studies have demonstrated that microscopically positive (R1) margins after resection can be associated with worse prognosis, although the prognostic effect can differ between early-and advanced-stage gc [25][26][27][28][29][30][31] . On multivariate analysis, the predictors for a positive margin include higher T stage, higher N stage, larger tumour size, and diffuse histologic type 24,[28][29][30] .…”
Section: Summary Of Evidencementioning
confidence: 99%